Comparison of Nebulized vs Systemic Corticosteroids for Management of Children Presenting with Acute Exacerbation of Asthma: Nebulized vs Systemic Corticosteroids for acute exacerbation of Asthma - Zaffar, MUhammad Usman; Waqas Ahmad; Nadeem Iqbal (Medical Journal of South Punjab, 2023)
Objective: is to compare the effectiveness of nebulized and systemic corticosteroids for management of acute exacerbation of asthma in children. Methodology: This randomized control trial was conducted at emergency department of Agha Khan University Hospital, Karachi in 6 months duration from 1st July 2021 to 30th December 2021. A total of 90 patients were emrolled in study and divided into two groups I and II. In group I nebulized corticosteroids were administered and in group II systemic corticosteroids were administered. Final outcomes were assessed after 2 weeks post treatment follow up. Results: Comparison of disease reduction (pre-treatment) of both the groups was shown in table II. Oscillometric Resistances at 1st day, 7th day and 14th day were almost equal in both the groups, (p>0.010). The mean length of stay of group I and group II was 1.75±0.56 days and 3.62±1.44 days, respectively, (p<0.001). most of the patients of group I were satisfied as compare to group II, 42 (93.3%) and 34 (75.6%), respectively, (<0.001). Conclusion: Use of nebulized steroids and systemic steroids can both be effective in the treatment of acute exacerbation of asthma, but their specific roles and benefits may vary depending on the individual patient’s condition and the severity of the exacerbation. Specific outcomes of hospital stay and severity of disease are much better in inhaled steroids as compare to systemic steroids.